Answer:
81
Step-by-step explanation:
6 over 12 equals 3 over 6 6 over 3 equals 6 over 12 6 over 6 equals 3 over 12 12 over 6 equals 3 over 6
Hello there the answer to your question would be 60. Since 150-(60%*150) = 150 - 60 *150 = (1-60%)*150 = (100%-60%) * 150= 40% * 150 = 40/100 * 150 = 40 * 150 ÷ 100 = 6000/100 = 60. Hope this helps you out, have a great day!
Answer:
The two inequality are : x ≤ 100 and x ≥ 60
So the inequality is : 60 ≤ x≤ 100.
Step-by-step explanation:
Answer:
play a game it will help
Step-by-step explanation:
Answer:
The answer is 120
Step-by-step explanation: